Diode laser cavity ring-down spectroscopy for in situ measurement of NO3 radical in ambient air. (November 2015) - Wang, Dan; Hu, Renzhi; Xie, Pinhua; Liu, Jianguo; Liu, Wenqing; Qin, Min; Ling, Liuyi; Zeng, Yi; Chen, Hao; Xing, XingBiao; Zhu, Guoliang; Wu, Jun; et al.
Abstract: A cavity ring-down spectroscopy (CRDS) instrument for measuring atmospheric NO3 radical developed in our laboratory is presented in detail. Light from a red laser diode (661.85 nm) is coupled on-axis into an optical cavity formed by a pair of high-reflectivity mirrors ( R ≥99.9985%) to achieve an effective absorption path length of approximately 20 km. The detection limit of the NO3 radical determined by Allan variance for the field observation with high particles is approximately 3.2 pptv (2 σ, 10 s). The transmission efficiency of the NO3 radical in the system is calibrated, including the filter loss and surface loss. Moreover, measurable interferences from NO2, O3 and water vapor are also discussed. Considering the influence of inlet transmission efficiency and other factors, the instrument accuracy for NO3 radical measurement is approximately ±8% (1 σ ). The measurement of NO3 radical was performed at a suburb site in Beijing under the situation of high particles concentration (PM2.5 approximately several tens to 150 µg/m 3 ) from October 26 to November 11, 2014. The NO3 radical concentration during the period is relatively low with the maximum value of 38 pptv. The observation results on October 29, combining NO2, O3 and NO data, are briefly analyzed. The experimental results demonstrate that this compact CRDS instrument has the potential for NO3 radical measurements in the field with high particles. Highlights: A CRDS instrument for measuring atmospheric NO3 radical is presented in detail. The instrument for NO3 radical measurement is calibrated and tested. The measurable interferences are discussed and the instrument accuracy is analyzed. The measurement of NO3 radical was performed under the situation of high particles.